2006
DOI: 10.1111/j.1741-3729.2006.00432.x
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence of Rural Aging Women*

Abstract: Although reports of intimate partner violence (IPV) decrease with age, a significant number of aging women experience IPV in their relationships. The structure and culture of rural environments may inadvertently conceal violence against aging women and inhibit prevention and treatment efforts. Guided by an ecological community framework, 3 focus groups involving 24 professionals working with victims of IPV in rural Kentucky and in-depth interviews with 10 aging rural women who had experienced IPV were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
118
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(128 citation statements)
references
References 20 publications
2
118
0
8
Order By: Relevance
“…Isolation, increasing dependence, and lack of physical or monetary resources to provide alternatives may keep an older adult in an abusive situation. Unfortunately, resources for obtaining help may be quite limited in rural areas (Teaster, Roberto, & Dugar, 2006). Thus, clinicians need to be sensitive to the problem and trained to handle it.…”
Section: Older Adults and Their Caregiversmentioning
confidence: 99%
“…Isolation, increasing dependence, and lack of physical or monetary resources to provide alternatives may keep an older adult in an abusive situation. Unfortunately, resources for obtaining help may be quite limited in rural areas (Teaster, Roberto, & Dugar, 2006). Thus, clinicians need to be sensitive to the problem and trained to handle it.…”
Section: Older Adults and Their Caregiversmentioning
confidence: 99%
“…Research on family and gender issues has analyzed intimate partner violence (IPV) reaching different conclusions (Teaster et al, 2006;Valls et al, 2008Valls et al, , 2016Yount and Li, 2009;Martin et al, 2013;Medrano et al, 2017;Vidu et al, 2017). One of these conclusions concerns on the central role that socialization process has in the reproduction of this problem.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, several researchers have suggested that an ecological view of older women and violence is needed (Heise, 1998;Horsford, Parra-Cardona, Post, & Schiamberg, 2011;Penhale, 2003;Teaster, Roberto, & Dugar, 2006). An ecological view indicates that violence takes place in interconnecting systems, each of which impacts the others (Bronfenbrenner, 2005).…”
Section: Discussionmentioning
confidence: 97%